2011
DOI: 10.1007/s11738-011-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular wax load and surface wettability of leaves and fruits collected from sweet cherry (Prunus avium) trees grown under field conditions or inside a polytunnel

Abstract: In this work, the effect of microclimate at the tree level inside a polytunnel and in an uncovered orchard of Prunus avium was studied through the observation of leaf and fruit micromorphology and the accumulation of cuticular waxes. Records of environmental parameters showed a significantly higher daytime temperature in the polytunnel (on an average 4°C), whereas the night temperature did not differ between treatments. Furthermore, photosynthetic active radiation and UV-B radiation inside the polytunnel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous studies found that the cuticular wax in rice leaf has a total amount of 8.35 µg/cm 2 and consists of 34.3% fatty acids (mainly C24–C32), 31.2% aldehydes (mainly C30–C34), 23.9% primary alcohols (mainly C30), 6.9% alkanes and 8.35% esters, dominated by relative non‐polar components . In addition to chemical effects, microstructure and nanostructure on the leaf surface, which is generally agreed as the key for the hydrophobicity of surfaces, has been reported as having a clear relationship with the chemical composition of the cuticular waxes . Former studies of the morphology of rice leaf surface have shown that the surface is covered with smaller convex sculptures (insert) and wax platelets, causing superhydrophobicity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that the cuticular wax in rice leaf has a total amount of 8.35 µg/cm 2 and consists of 34.3% fatty acids (mainly C24–C32), 31.2% aldehydes (mainly C30–C34), 23.9% primary alcohols (mainly C30), 6.9% alkanes and 8.35% esters, dominated by relative non‐polar components . In addition to chemical effects, microstructure and nanostructure on the leaf surface, which is generally agreed as the key for the hydrophobicity of surfaces, has been reported as having a clear relationship with the chemical composition of the cuticular waxes . Former studies of the morphology of rice leaf surface have shown that the surface is covered with smaller convex sculptures (insert) and wax platelets, causing superhydrophobicity .…”
Section: Discussionmentioning
confidence: 99%
“…Except for the influence of plant development, environment factors were also reported to influence the wettability of leaf surfaces such as environmental pollutant, the infestation of pests, and changes in temperature and humidity . So some measurements should be taken so as to adjust the pesticide formulation to adapt the plants surface wettability changes with growth process of crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there remain some differences in structure between the adaxial and abaxial foliar cuticles of most plants, especially angiosperms, the stomas of which are typically located in the abaxial epidermis [9]. The adaxial and abaxial cuticular topographies are distinct from each other resulting in different pollutant uptake behaviors [16,17]. Stomata located in abaxial cuticle was suggested to contribute importantly in the uptake of chemicals by plants, as the pore structures would offer a rapid access of toxicants to the deeper cuticle parts [18].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a cuticle surrounded by a waxy layer can control moisture transpiration, enhance mechanical properties, prevent invasive bacteria and reduce the adhesion of insects . The chemical composition, morphology and quantity of the waxy layer change with plant species and environmental factors such as temperature, humidity, drought stress, atmospheric pollutants and other non‐biological factors . Chemical composition, microstructure geometry and epiphytic surface material are major factors that influence leaf surface wettability .…”
Section: Introductionmentioning
confidence: 99%